Increased tissue factor and thrombomodulin expression and histopathological changes in placentas of pregnancies with preeclampsia (2020)
Abstract Introduction: Preeclampsia has a global frequency of 2-8% and a frequency of 10% in developing countries. In Colombia, preeclampsia causes 42% of maternal mortality. Alterations in placental homeostasis have been proposed to be involved in its pathophysiology. The aim of this study was to compare mRNA and protein levels of tissue factor (F3) and thrombomodulin (THBD) and the histopathological findings of placentas. Materials and methods: We studied 16 placentas from patients with preeclampsia and 19 term placentas with uncomplicated pregnancy. An expert pathologist, who was masked to the group assignment, conducted an evaluation to determine specific histological changes. Assessments of mRNA and protein levels of F3 and THBD were performed using real-time PCR and ELISA, respectively. Results: Cases and controls differed in the frequency of decidual arteriopathy (p = 0.027), acute infarction (p = 0.001) and hyperplasia of the syncytiotrophoblast (p = 0.0017). Cases had increased levels of F3 mRNA (p = 0.0124) and protein (p < 0.0001) and THBD mRNA (p < 0.0001) and protein (p < 0.0001). Conclusion: In placenta of patients with preeclampsia, we detected abnormal expression of F3 and THBD with increased protein and mRNA levels. The role of these molecules in the pathogenesis of this disease and in alterations of hemostatic and histopathological aspects of placentas need further studying.